Nutrição mineral e qualidade do fruto do abacaxizeiro e do maracujazeiro - Aular, Jesus; Casares, Maria; Nalale, William [UNESP] (Soc Brasileira Fruticultura, 2014)
Several factors influence the productivity and fruit quality of pineapple and passion fruit, among which are: climate, soil fertilization and irrigation practices. Mineral nutrition is essential to increase productivity and improve fruit quality; however, there is a few information about the effect of fertilization in these two fruit crops, especially under tropical conditions. The objective of this review was to compile the main research results, in which the influence of mineral nutrition on the fruit quality was evaluated. We considered the information recently published in scientific journals, and presented it for the macronutrients individually, then to NPK and, finally, the micronutrients. The review showed that it is difficult to say that some element favors or not certain characteristics of pineapple and passion fruit fruits, since the results are inconsistent and there is not many information. More than established the effects of mineral nutrients on the fruit quality of these two fruit crops, we stand out that research in this topic is very necessary.

Vários fatores influenciam a produtividade e a qualidade dos frutos do abacaxizeiro e do maracujazeiro, dentre os quais se destacam: o clima, o solo e as práticas de adubação e de irrigação. A nutrição mineral é essencial para elevar a produtividade e melhorar a qualidade dos frutos; no entanto, há poucas informações sobre o efeito da adubação nestas duas frutíferas, especialmente sob condições tropicais. O objetivo desta revisão foi compilar e apresentar os principais resultados de pesquisas, nas quais foi avaliada a influência da nutrição mineral sobre a qualidade destas duas frutíferas. Consideraram-se as informações publicadas recentemente em revistas científicas, sendo as mesmas apresentadas para os macronutrientes de forma individual, em seguida para N-P-K e, por último, para os micronutrientes. A revisão da literatura mostrou que é difícil afirmar que algum elemento favorece ou não determinada característica dos frutos do abacaxizeiro e do maracujazeiro, já que os resultados são variáveis ou existe pouca informação. Em função disso, mais do que deixar estabelecidos os efeitos dos elementos minerais sobre a qualidade dos frutos, o que chama a atenção é a necessidade de pesquisar sobre este tema.
Mineral nutrition and fruit quality of pineaple and passion fruit
Keywords: Ananas comosus L. Merril; Passiflora edulis f. Flavicarpa Deg.; Macronutrient; Micronutrient; Ananas comosus L. Merril; Passiflora edulis f. Flavicarpa Deg.; Macronutrientes; Micronutrientes